Pengaruh Minyak Ikan Lemuru (Sardinella longiceps) terhadap Ekspresi Tumor Necrosis Factor (TNF-α) Kartilago yang Diinduksi Complete Freund's Adjuvant (Effect of Lemuru (Sardinella longiceps) Fish Oil on Tumor Necrosis Factor (TNF-α) Expression of Cartilage that Induced by Complete Freund's Adjuvant) - Kiki Andari; Rena Normasari; Muhammad Hasan (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Osteoarthritis is a chronic joint disorder with weakening and disintegration of the joint cartilage followed by the growth of new bone and cartilage. TNF-α is one of the inflammatory mediator that plays an important role in the progression of osteoarthritis. In the others hands, lemuru (Sardinella longiceps) fish oils that contain EPA and DHA has an anti-inflammatory effect. The purpose of this study was to investigate the effect of lemuru fish oil on decreasing the expression of TNF-α in cartilage that induced by Complete Freunds Adjuvant. This was a experimental design study with randomized post test only control group design. The sample was divided into 2 groups: the negative control group (K-) and the treatment group (P), each group was divided into three subgroups based on duration of lemuru fish oils treatment, 7th, 14th and 21st days. TNF-α expression data was obtained from immunohistochemical observations on tibiofemoral articular cartilage. The result showed that the expression of TNF-α in the treatment group is lower than the negative control group and One Way Anova test showed that there is significant difference between groups (p = 0.000). We can conclude that lemuru (Sardinella longiceps) fish oil decreased the expression of TNF-α. Keywords: Osteoarthritis, TNF-α, lemuru (Sardinella longiceps) fish oil, cartilage